Estimating domestic self-supply groundwater use in urban continental Africa. (12th October 2020) - Chávez García Silva, Rafael; Grönwall, Jenny; van der Kwast, Johannes; Danert, Kerstin; Foppen, Jan Willem
Abstract: Self-supply of groundwater for domestic use in urban sub-Saharan Africa (SSA) is common, but the extent to which it is practiced is unknown. We developed an open data based GIS method for continental Africa (without islands) using groundwater storage, depth to groundwater, aquifer productivity, and population density data. Furthermore, we developed proxies for public supply network coverage and socio-economic status, incorporating restriction measures for groundwater use. Our results indicate that in 2015 about 369 million urban inhabitants (∼79% of the total urban population) of continental Africa could potentially supply themselves with groundwater. However, the likely number of urban inhabitants using groundwater obtained via self-supply was less: about 150 million (∼32% of the total urban population). With the novel GIS based methodology presented here, the urban population using self-supply groundwater for domestic use can be determined, which is essential to inform policy and practice, and to influence public investment.